Pengaruh Suhu dan Lama Penyangraian Terhadap Sifat Fisik Kopi Robusta Tempur - Shodiq Eko Ariyanto; Heny Alpandari; Suharijanto; Hendy Hendro Hadi Sridjono (Jurnal Galung Tropika, 2024)
Coffee roasting is a step in shaping the aroma and flavor of coffee beans, which is done through heating at high temperatures. Only now, information on the optimal roasting method to create quality coffee is limited. In some conditions, there is a decrease in coffee quality due to the overroast process. This study was conducted to determine the effect of temperature and roasting time on changes in the physical properties of Robusta coffee. The research design used was a Factorial Completely Randomized Design (CRD) with the treatment of variations in temperature and roasting time consisting of three levels, namely roasting temperature consisting of 100 °C, 110 °C, and 120 °C. In contrast, the roasting time consisted of 75 minutes, 80 minutes, and 85 minutes. Each treatment was replicated three times so that 27 experimental units were obtained. Based on the results of research on temperature treatment and roasting time, 100 °C treatment for 85 minutes gave better results on the parameters of water content, solubility, color, taste, and overall. It was followed by 110 °C temperature treatment for 75 minutes.